Biomarkers of Fish Oil Omega-3 Polyunsaturated Fatty Acids Intake in Humans. (February 2014) - Silva, Veronica; Barazzoni, Rocco; Singer, Pierre
A biomarker is a measured characteristic that may be used as an indicator of some biological state or condition. In health and disease, biomarkers have been used not only for clinical diagnosis purposes but also as tools to assess effectiveness of a nutrition or drug intervention. When considering nutrition studies, evaluating the appropriate biomarker is a useful tool to assess compliance and incidence of a particular dietary component in the biochemistry of the organism. Fish oil is rich in ω-3 fatty acids that have well-known beneficial effects on human health mainly through its anti-inflammatory properties. It has been widely use to improve health and as a nutrition supplement in different pathological conditions such as cardiovascular, neurological, and critically ill related diseases. Eicosapentaenoic acid and docosahexaenoic acid levels present in different biological moieties (plasma, cellular membranes, adipose tissue, etc) are the best biomarkers of fish oil intake. Each biological source of fatty acids has its own advantages and disadvantages, thus which biomarker to choose and where to measure it requires a comprehension of the objectives of the investigation. In this article we will review key facts about fish oil intake biomarkers to evaluate how components of a specific diet could be monitored and identified in biological samples. Having an accurate assessment of nutrition patterns could provide effective targets for intervention aimed at modifying eating habits and lifestyle towards the improvement of health.